Case of anesthetic management of a patient with sickle cell disease for pericardiectomy: anterior pericardiotomy and avoiding cardiopulmonary bypass - Parajuli, Santosh Sharma (Journal of Society of Anesthesiologists of Nepal, 2019)
Patients having sickle cell disease can land up to the anesthetist for various purposes like surgery, acute pain management and intensive care for acute respiratory failure. Our case was of a 20-year-old female patient presented with anemia and symptoms of constrictive pericarditis. Following investigations, which were also suggestive of sickle cell disease, she was planned for pericardiectomy under general anesthesia. We performed anterior pericardiectomy rather than a complete pericardiotomy to avoid cardiopulmonary bypass and to decrease the chance of postoperative complications.